2006
DOI: 10.1111/j.1439-0310.2006.01263.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Rearing Conditions Affect the Development of Body Size and Song in Bengalese Finches

Abstract: Birdsong is an acoustic ornament. According to indicator models, a trait must be costly to act as an honest signal, but the potential costs of elaborate songs are still poorly understood. The developmental stress hypothesis suggests that learned song characteristics could be an honest indicator of early developmental conditions because the brain structures associated with learning songs are susceptible to early developmental stress, which could thus affect song development. Unlike previous studies of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 39 publications
(45 reference statements)
3
40
0
Order By: Relevance
“…domestica, belongs to the same family (Estrildidae) as the zebra finch, but shows opposite sex-specific vulnerability. We found that male chicks were more likely to suffer from sibling competition in larger broods than females (Soma et al, 2006), because of the relatively higher growth rate of males (Soma et al, 2007). Thus, in Bengalese finches, having sons is more expensive for parents, but might lead to a higher fitness return in exchange for considerable reproductive investment.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…domestica, belongs to the same family (Estrildidae) as the zebra finch, but shows opposite sex-specific vulnerability. We found that male chicks were more likely to suffer from sibling competition in larger broods than females (Soma et al, 2006), because of the relatively higher growth rate of males (Soma et al, 2007). Thus, in Bengalese finches, having sons is more expensive for parents, but might lead to a higher fitness return in exchange for considerable reproductive investment.…”
Section: Introductionmentioning
confidence: 77%
“…It has been shown in Bengalese finches that these song features reflect early developmental conditions when song learning takes place, but are not related to body conditions in adulthood (Soma et al, 2006). By contrast, song duration is more plastic within individuals, and is known to reflect the body size of individuals (Soma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations